Pelaksanaan Layanan Konseling Kelompok Dengan Teknik Token Economy Untuk Meningkatkan Disiplin Belajar Siswa di SMP Negeri 11 Muaro Jambi - Okta Anira Radika; Nelyahardi Gutji; Hera Wahyuni (Departement of Mathematics Education, 2023)
Abstract Study discipline is very important to apply in everyday life, but it is also often a problem for students at school. Various violations regarding study discipline such as not being disciplined in time and not obeying school rules very often occur among school students. Based on direct observation at SMP Negeri 11 Muaro Jambi, the results show that the level of discipline in class VIII students shows low results. That is, there is a lot of indiscipline committed by class VIII students. Using a modification of the Token Economy Technique in group counseling services can increase the level of student discipline. The purpose of this research is to improve student learning discipline at school through group counseling services with a modification of the Token Economy Technique at SMP Negeri 11 Muaro Jambi. The sampling criterion was purposive sampling with a total of 10 class VIII students. This research was conducted in 3 cycles with each cycle consisting of 2 actions. This study consists of four competencies for each cycle, namely planning, implementing, evaluating, and reflecting. The results showed that there was an increase in student discipline behavior in each cycle. In cycle I the researchers conducted group counseling where the average percentage gain was 23% which was in the